A Review on the Impact of Humidity during Electrospinning: From the Nanofiber Structure Engineering to the Applications. Issue 7 (19th April 2021) - Mailley, Domitille; Hébraud, Anne; Schlatter, Guy
Abstract: Electrospinning is the process of choice for the elaboration of nanofibrous mats. During the process, a thin and continuous charged jet of a polymer solution is traveling from an emitter subjected to a high voltage toward a grounded collector. Although the duration of the jet travel is in the order of few tens of milliseconds, the physical interactions acting between the jet and the air play a key role on the resulting fiber morphology. These interactions mainly rely on the amount of water molecules in air. This review deals with the effect of humidity during electrospinning on solvent evaporation, the solidification rate of nanofibers and finally, on the morphology at length scales ranging from the non‐woven mat, the nanofiber itself down to the polymer crystal. Original electrospinning processes operating under specific environmental conditions as well as specificities encountered in needleless and free‐surface electrospinning dedicated to industrial‐scale mass production are also discussed. Then, it is shown how the control of humidity during electrospinning and the understanding of its influence on the fibrous structure can be exploited to target various applications dedicated to energy, environment, and health. Finally, current challenges and ideas for future research and new developments are presented. Abstract : This review discusses the effect of humidity during electrospinning on solvent evaporation, nanofiber solidification and the morphology at the length scales ranging from the nonwoven mat, the nanofiber down to the polymer crystal. The control of humidity during electrospinning can be exploited to target various applications. Current challenges and ideas for future research and new developments are finally presented.